SANKSI PIDANA TERHADAP BADAN USAHA YANG MENGANGKUT MINYAK BUMI TANPA MEMILIKI IZIN USAHA PENGANGKUTAN - Hartika Sari, Juniar (Fakultas Hukum Universitas IBA Palembang, 2024)
ABSTRACT Oil and Natural Gas are one of the greatest natural resources owned by Indonesia. Mining, Indonesia produces Oil and Natural Gas which are strategic natural resources that are renewable (exhausted) and are vital commodities that affect the lives of many people. This commodity also has an important role in the national economy so that its management must be able to optimally provide prosperity and welfare for the people. As legal research carried out by reviewing library data, the research I conducted is Normative legal research. The normative legal research examined is only library materials or secondary data which may only include primary, secondary and tertiary legal materials. Sanctions for business entities that transport petroleum without a business permit are regulated in Article 56 of Law No. 22 of 2001, namely a fine plus one third of the basic penalty. Referring to Article 30 paragraph (2) of the Criminal Code, if a business entity that has been proven to have committed a criminal offense does not pay the fine, it is replaced with imprisonment, but what happens if the business entity does not pay the fine, what kind of sanctions can be applied.